A fungal symbiont converts provisioned cellulose into edible yield for its leafcutter ant farmers. (20th April 2022) - Conlon, Benjamin H.; O'Tuama, David; Michelsen, Anders; Crumière, Antonin J. J.; Shik, Jonathan Z.
Abstract : While ants are dominant consumers in terrestrial habitats, only the leafcutters practice herbivory. Leafcutters do this by provisioning a fungal cultivar ( Leucoagaricus gongylophorus ) with freshly cut plant fragments and harnessing its metabolic machinery to convert plant mulch into edible fungal tissue (hyphae and swollen hyphal cells called gongylidia). The cultivar is known to degrade cellulose, but whether it assimilates this ubiquitous but recalcitrant molecule into its nutritional reward structures is unknown. We use in vitro experiments with isotopically labelled cellulose to show that fungal cultures from an Atta colombica leafcutter colony convert cellulose-derived carbon into gongylidia, even when potential bacterial symbionts are excluded. A laboratory feeding experiment showed that cellulose assimilation also occurs in vivo in A. colombica colonies. Analyses of publicly available transcriptomic data further identified a complete, constitutively expressed, cellulose-degradation pathway in the fungal cultivar. Confirming leafcutters use cellulose as a food source sheds light on the eco-evolutionary success of these important herbivores.